ISO 9001 : 2000 development in a manufacturing company [electronic resource] - 454970 Lim, Chea Woong (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2006